Ear Reconstruction with Preauricular Transposition and Helical Chondrocutaneous Advancement Flap After Excision of Trichilemmal Carcinoma - Yaşar Kemal Duymaz (The Turkish Journal of Ear Nose and Throat)
Trichilemmal carcinoma (TLC) is a fairly uncommon cutaneous malignancy with a favorable prognosis in the majority of cases. The gold standard of treatment is extensive local excision. The purpose of this study is to demonstrate the outcomes of a single-stage surgical approach that preserves the ear’s anatomical characteristics. We present a case of a 70-year-old man who was treated with a single-stage surgical technique for trichilemmal cancer of the ear. After six months, the ear seemed to have entirely healed with no evidence of recurrence.